THE IMPACT OF CASH FLOW AND AUDIT QUALITY AFFECTING PROFIT MANAGEMENT THROUGH ACCRUAL TRANSACTION OF LISTED COMPANIES IN THE STOCK EXCHANGE OF THAILAND: A CASE STUDY PROPERTY & CONSTRUCTION INDUSTRY - Wongwaengnoi, Yuwadee (Journal of MCU Nakhondhat, 2020)
The research articles of the impact of cash flow and audit quality affecting profit management through accrual transaction of listed companies in the Stock Exchange of Thailand: a case study Property & Construction Industry had purposive to study the impact of cash flow and the quality work affecting profit management through accrual transaction of listed companies on the Stock Exchange of Thailand: Property & Construction Industry. Using information from financial statements, annual report and annual registration statement (form 56 – 1) between 2014 and 2018. The sample group is 63 Property & Construction Industry which listed companies on the Stock Exchange of Thailand. Using descriptive statistics such as maximum, minimum, mean and standard deviation, and inferential statistics, including Pearson’s Correlation Coefficient and Multiple Regression Analysis. The research found that; the cash flow were operating activities, investment activities and financing activities affecting the profit management through open items from business operations and accrual transaction at the discretion of the management of companies registered in the Stock Exchange of Thailand: Property & Construction Industry was at .01 statistical significance level. The quality of the audit is the size of the audit firm, examination fee and duration of service affecting the profit management through accrual transaction from business operations and accrual items at the discretion of the management of companies listed on the Stock Exchange of Thailand: Property & Construction Industry was at .01statistical significance level.